Optimization of ultrasound-electrocatalytic process for improving the quality of biological treatment effluent - Parviz Abdi; Kobra Verdijkazemi; Arezoo Nejaei; Afshin Takdastan (Scientific Reports)
Abstract Improving the quality of biologically treated effluent could encourage the reuse of wastewater. It is uncommon to use enhanced electrochemical oxidation techniques to improve effluent. Using hydrothermal reaction with complicated precipitation, the work generated FTO-TiO2/Ni anodes and analyzed them with the following methods: TEM, FESEM, EDS, elemental mapping, XRD, FTIR, and CV analysis. A 500 mL sono-electrocatalyst process reactor was used with central composite design in order to achieve the greatest decrease in COD. The reaction kinetics, synergistic effect of mechanisms, physicochemical properties of wastewater after the process, energy efficiency, and toxicity of wastewater were all investigated under ideal conditions. The anode electrode analyses indicate that the synthesis is sufficient. The quadratic model is noteworthy because of the P-value (0.0001) and the F-value (600.39). The correlation coefficients were much greater than the values obtained for the other model. The experimental settings were pH 7.1, 74.4 mA/cm2 DC power, 15 mW/cm2 applied USI, and a reaction time of 112 min (COD reduction = 81.5%). Chemical reactions follow first-order kinetics (R2 = 0.99). The synergistic coefficients for the pathways were 1.6 for COD, 2.2 for BOD5, and 1.5 for TOC. After 300 min, the energy efficiency was 1.07 kWh/m3, and the toxicity of the effluent was reduced to 5%. The above technique was shown to be a feasible advanced treatment that can improve effluent discharge, according to this study.